Analysis of The Implementation of School Culture on The Formation of Student Attitudes in State Elementary School 05 Bengkulu City - Sabillah Audina Putri; Thasiya Annisa Putri; Heny Friantary; Ade Bayu Saputra (Yayasan Azhar Amanaa Yogyakarta, 2025)
This study aims to analyze the implementation of school culture in improving student attitudes at SD Negeri 05, Bengkulu City. School culture is seen as an important component in forming positive habits, fostering discipline, politeness, responsibility, and social awareness among students. This study uses a qualitative descriptive method with data collection techniques through observation, interviews, and documentation. The research subjects consisted of the principal, teachers, and students. The results of the study indicate that school culture at SD Negeri 05, Bengkulu City has been implemented through the habit of greeting, smiling, greeting, praying together, maintaining environmental cleanliness, and implementing school regulations, although the implementation still faces several challenges. This study recommends that the school continue to strengthen the implementation of school culture through a habituation program that is carried out consistently and continuously. Teachers are expected to be role models in applying the values ​​of discipline, responsibility, politeness, and social awareness to students and conduct regular evaluations of the implementation of school culture so that the implemented program can run more effectively in improving student attitudes.